Two new species of the genus Zorochros (Coleoptera: Elateridae: Negastriinae) from Korea - Han, Taeman; Park, In Gyun; Park, Haechul (Zootaxa, 2015)
Two new species of the genus Zorochros are described from Korea: Zorochros (Zorochros) coreanus sp. nov. and Z. (Z.) mansusanensis sp. nov., belonging to the Z. (Z.) alysidotus species group and Z. (Z.) meridionalis species group, respectively. A key to the Eurasian species for the Z. alysidotus group (nine species) and the Z. meridionalis group (five species) is provided with illustrations of the two new species and their closely allied species, Z. (Z.) mesatiaticus Dolin and Z. (Z.) gurjevae Dolin from Kazakhstan.